Official Launching of UMP Confucius Institute - UMP, PNC (2019)
The launching of Universiti Malaysia Pahang (UMP) Confucius Institute (CI) reflected the university’s serious effort in providing education and training in technical and vocational (TVET) in a Mandarin learning setting